METHODOLOGICAL ASPECTS OF DEVELOPING METHODS OF INDEPENDENT EDUCATIONAL ACTIVITY OF FUTURE TEACHERS IN THE ENVIRONMENT OF DIGITAL EDUCATION (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical foundations of the development of the methodology of independent educational activities of future teachers in digital education, the pedagogical content of the methodology of independent educational activities of future teachers in digital education, the effectiveness of the development of the methodology of independent educational activities of future teachers in digital education. Also, the methodological aspects of the development of the methodology of independent educational activities of future teachers in digital education are analyzed